Preliminary study on compressive strength of modified Polystyrene (MPS) as lightweight aggregate - Fetra Venny Riza, Z; Mohd Mustafa Al Bakri, Abdullah; Khairul Nizar, Ismail; Che Mohd Ruzaidi, Ghazali; Mohammad Tamizi, Selimin (Universiti Malaysia Perlis, 2009)
Organized by Universiti Malaysia Perlis, 15th - 16th March 2008 at Putra Palace Hotel, Perlis.